Treatment for central-peripheral rivalry-type diplopia (“dragged-fovea diplopia syndrome”) - Hatt, Sarah R. (Am J Ophthalmol, 2019)
PURPOSE: To report the effectiveness of treatments for central-peripheral rivalry (CPR)-type diplopia due to retinal misregistration. DESIGN: Retrospective, interventional case series SETTING: Adult strabismus clinic at a tertiary medical center PATIENT POPULATION: 50 adults with retinal misregistration and CPR-type diplopia (minimum frequency of “sometimes” at distance and/or for reading), caused by epiretinal membrane (n=44) or other retinal disorders (n=6). INTERVENTIONS: Included treatments were: Bangerter filter, tape, Fresnel prism, clear prism (incorporated into glasses or loose prism in office), iseikonic manipulation (using iseikonic lenses or contact lenses), MIN lens, or epiretinal membrane peeling (alone or in any combination). Not all treatments were trialed on all patients. MAIN OUTCOME MEASURES: Diplopia frequency evaluated using the Diplopia Questionnaire. Success was defined as “never” or “rarely” diplopic for distance and reading using the Diplopia Questionnaire, at an outcome examination as close as possible to 6 months. RESULTS: Overall, 17 (34%, 95% CI 21% to 49%) of 50 patients were classified a success: Fresnel prism 4 (57%, 18% to 90%) of 7 patients; Bangerter filter 4 (14%, 4% to 33%) of 28, epiretinal membrane peeling 8 (44%, 22% to 69%) of 18 patients, and iseikonic manipulation (using a contact lens) 1 (4%, 0% to 22%) of 23 patients. CONCLUSIONS AND RELEVANCE: CPR-type diplopia may be relieved in some patients using non-surgical treatment options of Fresnel prism or Bangerter filter. ERM peeling was surprisingly successful and should be considered.